Efficient Execution of Networked MPSoC Models by Exploiting Multiple Platform Levels. (18th September 2012) - Roth, Christoph; Meyer, Joachim; Rückauer, Michael; Sander, Oliver; Becker, Jürgen
Abstract : Novel embedded applications are characterized by increasing requirements on processing performance as well as the demand for communication between several or many devices. Networked Multiprocessor System-on-Chips (MPSoCs) are a possible solution to cope with this increasing complexity. Such systems require a detailed exploration on both architectures and system design. An approach that allows investigating interdependencies between system and network domain is the cooperative execution of system design tools with a network simulator. Within previous work, synchronization mechanisms have been developed for parallel system simulation and system/network co-simulation using the high level architecture (HLA). Within this contribution, a methodology is presented that extends previous work with further building blocks towards a construction kit for system/network co-simulation. The methodology facilitates flexible assembly of components and adaptation to the specific needs of use cases in terms of performance and accuracy. Underlying concepts and made extensions are discussed in detail. Benefits are substantiated by means of various benchmarks.